1962
DOI: 10.1063/1.1706515
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Production by Neutral-Atom Injection: Equations and Numerical Solutions

Abstract: Differential equations and their solutions for the formation of a high-energy plasma by the injection and trapping of energetic atoms in a magnetic-mirror geometry are discussed. The present approach differs from previous treatments in that the finite orbit size of the ions and the spatial dependence of the trapping process are included in the equations. By including the spatial dependence it was possible to evaluate the effect of charge exchange of trapped ions with neutral-beam atoms. Although not affecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1964
1964
1991
1991

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…In equations (1) and (2), we have neglected charge exchange of energetic trapped ions with neutral beam atoms. This process does not affect the total number of trapped ions and the resulting spatial redistribution of the hot ions does not significantly change the plasma growth rate (FUTCH et al, 1962). The contribution of inverted cascading (HISKES, 1963;KARPUSHKINA and GRECHUKIN, 1964) to the Lorentz-force trapping has been neglected here in the interest of simplification.…”
Section: D I F F E R E N T I a L Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In equations (1) and (2), we have neglected charge exchange of energetic trapped ions with neutral beam atoms. This process does not affect the total number of trapped ions and the resulting spatial redistribution of the hot ions does not significantly change the plasma growth rate (FUTCH et al, 1962). The contribution of inverted cascading (HISKES, 1963;KARPUSHKINA and GRECHUKIN, 1964) to the Lorentz-force trapping has been neglected here in the interest of simplification.…”
Section: D I F F E R E N T I a L Equationsmentioning
confidence: 99%
“…THE differential equations and their solutions for the formation of high energy plasma by the injection and trapping of energetic atoms in a magnetic-mirror geometry are well known (GIBSON et al, 1959;POST and DAMM, 1960;FUTCH et al, 1962;SWEETMAN, 1962). In a magnetic-mirror field, the cold ions (produced by chargeexchange collisions and by ionization of the background gas) may be neglected since they are rapidly scattered into the mirror escape cone and lost from the system.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 20 it was found that if the neutral beam is directed at the proper ~alf of the target plasma, the .Plasma losses by migration of guiding centers will be negligibly small. The study of these effects in LITE has been reserved for an analysis of the type described in Ref.…”
Section: Time-dependent Plasma Volumementioning
confidence: 99%
“…The remainder contributes to growth of the plasma volume or sustains it against charge exchange erosion. Now, since (20) (Ref.…”
Section: ~( Rg)mentioning
confidence: 99%
“…In the first case N(t) = N 0 (t) the density of cold neutrals next to the plasma, while in the second N(t) = Ny(t) the cold neutral density between the magnet and the vacu.um chamber wall. 20 it was found that if the neutral beam is directed at the proper ~alf of the target plasma, the .Plasma losses by migration of guiding centers will be negligibly small. The study of these effects in LITE has been reserved for an analysis of the type described in Ref.…”
Section: Saturation Of Getter Surfacesmentioning
confidence: 99%